2020
DOI: 10.1088/1751-8121/abd267
|View full text |Cite
|
Sign up to set email alerts
|

Alternative quantisation condition for wavepacket dynamics in a hyperbolic double well

Abstract: We propose an analytical approach for computing the eigenspectrum and corresponding eigenstates of a hyperbolic double well potential of arbitrary height or width, which goes beyond the usual techniques applied to quasi-exactly solvable models. We map the time-independent Schrödinger equation onto the Heun confluent differential equation, which is solved by using an infinite power series. The coefficients of this series are polynomials in the quantisation parameter, whose roots correspond to the system’s eigen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 38 publications
(83 reference statements)
2
24
0
Order By: Relevance
“…The quantum bridges could be controlled with the appropriate coherent superposition of states or different driving fields, which opens a wide range of possibilities for studying quantum effects in enhanced ionisation. We have verified that, for the model potential in [139], the frequencies computed analytically are quite robust upon inclusion of an external static field. This is illustrated in Fig.…”
Section: Understanding Timescalessupporting
confidence: 56%
See 4 more Smart Citations
“…The quantum bridges could be controlled with the appropriate coherent superposition of states or different driving fields, which opens a wide range of possibilities for studying quantum effects in enhanced ionisation. We have verified that, for the model potential in [139], the frequencies computed analytically are quite robust upon inclusion of an external static field. This is illustrated in Fig.…”
Section: Understanding Timescalessupporting
confidence: 56%
“…Further work, however, showed that the momentum gates are intrinsic to the molecular sys-tem and exist even for static fields, or no fields at all. Thereby, quantum interference plays an important role by providing a bridge for quasiprobability to flow from one molecular well to the other [78], and the frequencies can be estimated for double-well potential models [139]. Further studies of nonadiabatic effects and bifurcation in strong-field ionisation were conducted in [77].…”
Section: Tunnellingmentioning
confidence: 99%
See 3 more Smart Citations